Patterns of Organisational Justice Among Swedish Employees: Results From a Latent Profile Analysis - Constanze Leineweber; Paraskevi Peristera; Constanze Eib; Claudia Bernhard-Oettel (Scandinavian Journal of Work and Organizational Psychology)
Despite extensive research on organisational justice, it remains unknown how organisational justice aspects interrelate and co-occur in individuals. Using a person-centred approach, and latent profile analysis specifically, we examine profiles of procedural, distributive (as measured by effort-reward imbalance), interpersonal, informational, and overall justice. Profiles are validated with covariates as well as work and health outcomes cross-sectionally and prospectively over time. Data from the Swedish Longitudinal Occupational Survey of Health (SLOSH) from 2018 (n = 9,756) and 2020 (n = 7,542) were used. Based on data from 2018, we found four different profiles: an ‘Average justice’ profile, a ‘High justice’ profile, a ‘Low justice’ profile and a ‘Low process-focused justice’ profile. The ‘Low justice’ profile, especially, was comprised of a high proportion of women, lower educated, public-sector employees and shift workers. The ‘Low justice’ profile showed high levels of intentions to leave, suboptimal general health and low job satisfaction in 2018 and 2020. Results highlight the importance of organisational justice to maintain a healthy and motivated workforce and indicate that low levels of procedural justice might partly be mitigated by high levels of interactional justice. The study responds to the appeal by justice researchers to consider the experiential nature of justice perceptions and underscores the merit of moving beyond variable-oriented methods.